Fever of the Bone - McDermid, Val (London Sphere, 2010)
The murder and mutilation of teenager Jennifer Maidment is horrific enough on its own. But it's not long before Tony realises it's just the start of a brutal and ruthless campaign that's targeting an apparently unconnected group of young people. Struggling with newly- awakened ghosts of his own past, Tony battles to find the answers.
Keywords: Police psychologists